The flow of funds, 1960 - 1985 - O'Connell, Thomas (Statistical and Social Inquiry Society of Ireland, 1986)
This paper reviews the development over time of the financial surpluses/deficits of the different broad economic sectors, i.e., the personal sector, companies, government and the external sector. The form in which different sectors' financial surpluses/deficits are held is then reviewed, and this affords an opportunity to consider the evolution of various types of financial assets and liabilities since 1960. Data are obtained from both published and unpublished sources. A degree of estimation is required on occasion, and a number of somewhat arbitrary assumptions are necessary. For this reason, certain data are more "ball-park" than precise estimates. However, it is believed that the broad picture sketched is a reasonably reliable one.
Read before the Society, 24 April, 1986
Keywords: Flow of funds; Fiscal policy; 314.15